Techno-moral change through solar geoengineering: How geoengineering challenges sustainability - Benjamin Hofbauer (Prometheus)
This article brings a new perspective to the ethical debate on geoengineering through stratospheric aerosol injection (SAI), incorporating the emerging techno-moral change scholarship into the discussion surrounding sustainability. The techno-moral change approach can help us understand different ways in which technology might shape society. First, it helps highlight how values and norms are interrelated. Second, it shows that techno-moral change can happen even if the technology is in no way realized. Through the introduction of two techno-moral vignettes, two diametrically opposed ways in which SAI forces us to rethink sustainability and our relationship with nature are suggested. SAI could lead to a situation of entrenchment, wherein sustainability as a norm is undermined, or transformation where the necessity of acting according to sustainability is highlighted.